Construction of a one-step multiplex real-time PCR assay for the detection of serogroups A, B, and E of Pasteurella multocida associated with bovine pasteurellosis - Wang, Haojie; Xin, Lingxiang; Wu, Yang; Liu, Yan; Yao, Wensheng; Zhang, He; Hu, Yunhao; Tong, Rendong; Zhu, Liangquan (Frontiers in Veterinary Science, 2023)
Bovine pasteurellosis, caused by serogroups A, B, and E of Pasteurella multocida (Pm), is mainly manifested as bovine respiratory disease (BRD) and haemorrhagic septicaemia (HS). The disease has caused a great economic loss for the cattle industry globally. Therefore, identifying the Pm serogroups is critical for optimal diagnosis and subsequential clinical treatment, even epidemiological studies. Here, a one-step multiplex real-time PCR assay was established. Three pairs of specific primers were prepared to detect the highly conserved genomic regions of serogroups A (HyaD), B (bcbD), and E (ecbJ) of Pm, respectively. The results depicted that the method had no cross-reaction with other bovine pathogens (Mannheimia hemolytica, Escherichia coli, Listeria monocytogenes, Staphylococcus aureus, Salmonella Dublin, Mycobacterium paratuberculosis, IBRV,Mycoplasma bovis). The linear range (107 to 102 copies/μL) showed the R2 values for serogroups A, B, and E of Pm as 0.9975, 0.9964, and 0.996, respectively. The multiplex real-time PCR efficiency was 90.30%, 90.72%, and 90.57% for CartA, CartB, and CartE, respectively. The sensitivity results showed that the serogroups A, B, and E of Pm could be detected as low as 10 copies/μL. The repeatability results clarified that an intra-assay and an inter-assay coefficient of variation of serogroups A, B, and E of Pm was less than 2%. For the clinical samples, the detection rate was higher than the OIE-recommended ordinary PCR. Overall, the established one-step multiplex real-time PCR assay may be a valuable tool for the rapid and early detection of the serogroups A, B, and E of Pm with high specificity and sensitivity.